The anatomy of the extensive margin labor supply response - Spencer Bastani; Ylva Moberg; Håkan Selin (Uppsala University, Department of Economics, 2016)
No previous quasi-experimental paper has systematically examined the relationship between the extensive margin labor supply response to taxation and the employment level. We model the labor force participation margin and estimate participation responses for married women in Sweden using population-wide administrative data and a solid identification strategy. The participation elasticity is more than twice as large in the lowest-skill sample (with relatively low employment) as compared with the highest-skill sample (with high employment). Our analysis suggests that cross- and within country comparisons of participation elasticities always should be made with reference to the relevant employment level.
urn:nbn:se:uu:diva-301944
Keywords: H20; J22; 330; labor supply; social assistance; housing allowance; in-work tax credits; take up of transfer programs